PENGEMBANGAN UMKM MELALUI PELATIHAN STANDARD OPERATIONAL PROCEDURE MENUJU UMKM NAIK KELAS - Wicaksono, Bagas Satrio; Sholihah, Dewi Deniaty (Batara Wisnu : Indonesian Journal of Community Services, 2025)
The preparation of standard operating procedures (SOP) for UMKM is very important. The preparation of SOP has benefits in creating systematic, efficient and effective operations and can help maintain the stability of employee performance and the quality of the products produced. In Gubeng Village, there are many UMKM that do not have clear SOP. Based on this gap, SOP design and socialization activities were carried out on UMKM in Gubeng Village with the aim of providing insight and understanding of the importance of SOP in the Company and facilitating favorable conditions to realize each activity used in the method. This study includes data collection using observation, interviews and notes. In this study, the results obtained were SOP for purchasing raw materials, SOP for storing raw materials, SOP for the production process, SOP for storing products, SOP for selling products, SOP for distributing products